2009
DOI: 10.1523/jneurosci.3475-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Stimulus-Specific Adaptation of Cortical Neurons and Local Field Potentials in the Awake Rat

Abstract: Changes in the sensory environment are good indicators for behaviorally relevant events and strong triggers for the reallocation of attention. In the auditory domain, violations of a pattern of repetitive stimuli precipitate in the event-related potentials as mismatch negativity (MMN). Stimulus-specific adaptation (SSA) of single neurons in the auditory cortex has been proposed to be the cellular substrate of MMN (Nelken and Ulanovsky, 2007). However, until now, the existence of SSA in the awake auditory corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
128
5
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(158 citation statements)
references
References 74 publications
20
128
5
1
Order By: Relevance
“…First, most previous forms of SSA have been reported along the primary auditory pathway [inferior colliculus (Pérez-González et al, 2005), the medial geniculate body (Anderson et al, 2009) (E). Second, previous forms of SSA have been reported to diminish at ISIs longer than 2 s (Ulanovsky et al, 2003) or have only been studied at ISIs Ͻ2 s (Reches and Gutfreund, 2008;von der Behrens et al, 2009;Antunes et al, 2010), whereas the adaptation identified here is active and specific in ISIs as long as 60 s. To the best of our knowledge, a comparable adaptation has not been reported in the auditory system.…”
Section: Discussioncontrasting
confidence: 55%
“…First, most previous forms of SSA have been reported along the primary auditory pathway [inferior colliculus (Pérez-González et al, 2005), the medial geniculate body (Anderson et al, 2009) (E). Second, previous forms of SSA have been reported to diminish at ISIs longer than 2 s (Ulanovsky et al, 2003) or have only been studied at ISIs Ͻ2 s (Reches and Gutfreund, 2008;von der Behrens et al, 2009;Antunes et al, 2010), whereas the adaptation identified here is active and specific in ISIs as long as 60 s. To the best of our knowledge, a comparable adaptation has not been reported in the auditory system.…”
Section: Discussioncontrasting
confidence: 55%
“…The memory trace is the minimal ISI in which the response to a stimulus is not affected by it's preceding stimulus. SSA in the auditory cortex or the thalamus has been reported to diminish at ISIs longer than 2 s (Ulanovsky et al 2003) or has only been studied at ISIs < 2 s (von der Behrens et al 2009;Antunes et al 2010). Therefore, we can conclude that the information about the standard is stored in memory for only about 2 s. This poses a major problem because many examples of behavioral habituation have been reported with ISIs of tens of seconds to minutes, even for short duration stimuli (Thompson and Spencer 1966;Weinberger et al 1975;Bala and Takahashi 2000;Zimmer 2006;Glanzman 2009;Dong and Clayton 2006;Valentinuzzi and Ferrari 1997).…”
Section: The Memory Trace Problemmentioning
confidence: 99%
“…At the single-neuron level, the detection of rare stimuli is reflected by stimulus-specific adaptation (SSA), in which neurons respond strongly to rare stimulus while adapting to frequently occurring ones (Ulanovsky et al, 2003;Gutfreund and Knudsen, 2006;Reches and Gutfreund, 2008;Malmierca et al, 2009;von der Behrens et al, 2009;Antunes et al, 2010;Reches et al, 2010). SSA depends on the history of stimulation and on mechanisms operating at the inputs of the neuron rather than on activity-dependent mechanisms operating at the output of the neuron (Ulanovsky et al, 2003(Ulanovsky et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In the auditory brain, SSA has been linked to auditory memory, recognition of acoustic objects, and scene analysis (Nelken, 2004;Winkler et al, 2009). SSA to the frequency of the acoustic stimulus has been identified in the midbrain, thalamus, and cortex (Ulanovsky et al, 2003;Pérez-González et al, 2005;Gutfreund and Knudsen, 2006;Reches and Gutfreund, 2008;Malmierca et al, 2009;von der Behrens et al, 2009;Antunes et al, 2010;Reches et al, 2010;Taaseh et al, 2011). SSA is strong in nonlemniscal subcortical regions Malmierca et al, 2009;Antunes et al, 2010), but the primary auditory cortex (AC) is the first lemniscal station where it is widespread and strong (Ulanovsky et al, 2003).…”
Section: Introductionmentioning
confidence: 99%